2018
DOI: 10.1115/1.4040500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oil Viscosity on Self-Excited Noise Production Inside the Pilot Stage of a Two-Stage Electrohydraulic Servovalve

Abstract: The occurrence of self-excited noise felt as squealing noise is a critical issue for an electrohydraulic servovalve that is an essential part of the hydraulic servocontrol system. Aiming to highlight the root causes of the self-excited noise, the effect of oil viscosity on the noise production inside a two-stage servovalve is investigated in this paper. The pressure pulsations' characteristics and noise characteristics are studied at three different oil viscosities experimentally by focusing on the flapper-noz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…where F is the flow force on the flapper by the flow impingement from each nozzle, p 1 is the pressure at the inlet of the nozzle, p 0 is the discharged pressure, D N is the internal diameter of the nozzle, D f is the diameter of the flapper. Based on (10) and (11), the equivalent internal diameter of the nozzle D ND and the equivalent diameter of the flapper D fD for the case of the diamond nozzle can be given as…”
Section: Simulation On Nozzle-flapper Servo Valvementioning
confidence: 99%
“…where F is the flow force on the flapper by the flow impingement from each nozzle, p 1 is the pressure at the inlet of the nozzle, p 0 is the discharged pressure, D N is the internal diameter of the nozzle, D f is the diameter of the flapper. Based on (10) and (11), the equivalent internal diameter of the nozzle D ND and the equivalent diameter of the flapper D fD for the case of the diamond nozzle can be given as…”
Section: Simulation On Nozzle-flapper Servo Valvementioning
confidence: 99%
“…The terms N bubbles and n 0 represent the number of bubbles in the computational cell and the number of bubbles per unit volume of liquid. The following cavitation model developed by Schnerr and Sauer cavitation is applied in the numerical simulations [11], [28], [31], [35]. When the cavitation occurs, the mass conservation equation is governed by the vapor transport equations:…”
Section: Model Of Cavitationmentioning
confidence: 99%
“…Gao et al [10] studied the formation of the vortex and the flow stream inside metering in the spool valve with different valve openings by using finite element and PIV methods. Aiming to highlight the root causes of the self-excited noise inside the pilot stage of the flapper-nozzle servo valve, Chen et al [11] investigated the pressure pulsation characteristics and noise characteristics at three different oil viscosities experimentally. According to their results from both numerical simulations and experimental flow observations, it found that the cavitation shedding phenomenon is intensified with the decreasing of oil viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that when static pressure inside machinery reduces to a critical value the nuclei will be triggered and cavitation occurs. Since cavitation may reduce efficiency, generate vibration and acoustic noise, or even cause a catastrophic disaster [12,13], the hydraulic cavitation inside macro machinery has attracted enormous attention from researchers [13,14,15]. Although there are experimental and numerical investigations demonstrating that a microfluidic system with micro-orifices may suffer from the influences of cavitation, there are only a few that concentrate on cavitation inside a microfluidic system until now [16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%